La diosa des–alada. El cuerpo como espacio en el desplazado y sus narrativas de interpretación (2003)
In Colombia, due to the war for the territory and to violence, thousands of communities are submitted to forced displacements: this uncontrollable force which today, dislocates, expulses, de-situates millions of people from their spaces and submits them to the dictatorship of intolerance.In the text, The De-winged Goddess, the body is analyzed as a space and the problem of forced displacements is approached from an esthetical and communicational perspective. In the body expressions of the displaced person, there is a projective representation of his story, of his silent duels, the uncertainty that marks him, the problematic which in essence has restricted his liberty, and of the independence to be decided upon.